Impact of cytomegalovirus exposure on disease severity, bacterial burden, immune responses and treatment outcomes in tuberculosis - Dasan, Bindu; Munisankar, Saravanan; Kumar, Nathella Pavan; Moideen, Kadar; Pandiarajan, Arul Nancy; Nott, Sujatha; Viswanathan, Vijay; Shanmugam, Sivakumar; Hissar, Syed; Thiruvengadam, Kannan; Kornfeld, Hardy; Babu, Subash (Frontiers in Immunology, 2025)
IntroductionTuberculosis (TB) continues to be one of the leading causes of global mortality. Recent evidence highlights human cytomegalovirus (CMV) as a risk factor for TB. However, the impact of CMV exposure on disease severity, bacterial burden, and TB treatment outcomes remain poorly understood.MethodsSerostatus of CMV was determined by assaying IgG titers in plasma samples by ELISA. Chest X-rays were employed to assess bilateral lung lesions and cavitary diseases, and sputum smear grades to measure bacterial loads in TB subjects. Treatment outcomes were defined as favorable or unfavorable. Cytokine profiles were measured using multiplex ELISA.ResultsThe study revealed that TB patients with CMV seopositivity had significantly higher bacterial loads (adjusted PR [aPR], 4·14; 95% CI, 2·21-7·16; p<0·001), bilateral lung lesions (aPR, 2·97; 95% CI, 1·71-5·17; P<0·001), cavitary lung lesions (aPR, 4·21; 95% CI, 1·98-6·24; p<0·001) and unfavorable treatment outcomes (aPR, 1·48; 95% CI, 1·08-2·69; p=0·05). Our data also show that TB is associated with significantly lower levels of IFNγ, IL-2, TNFα, IL-1α, and IL-1β but significantly higher levels of IL-10, IFNα, IFNβ, G-CSF, and VEGF in CMV exposed individuals compared to CMV non exposed individuals.ConclusionOur findings reveal that CMV exposure worsens the severity of TB, increases bacterial burden, and leads to poorer treatment outcomes. The modulation of cytokine responses in TB patients with CMV exposure suggests a potential mechanism by which CMV may exacerbate TB pathogenesis.